Targeted muscle reinnervation - Kuiken, Todd A.; Feuser, Aimee E. Schultz.; Barlow, Ann K. (Series in medical physics and biomedical engineering ;, 2014)
"This reference covers clinical and bioengineering aspects of muscle reinnervation, a popular new technique at the boundary of biomedical and rehabilitation engineering and neuroscience. With contributions from pioneers in the field, the book provides a review of muscle reinnervation from a biomedical engineering and clinical perspective. It describes neuroscience and other related neuroprosthetic techniques. A companion website offers a wide range of videos and multimedia material to aid in comprehension and application"--Provided by publisher.